Synthesis, crystal structure, and computational investigation of zinc-cytosine coordination complex: insights from molecular docking, ADME prediction, HOMO-LUMO, and MEP analysis - Nagaraj, Karuppiah; Karthikeyan, A.; Velmurugan, Gunasekaran; Muthukkumar, M.; Devanesan, Sandhanasamy; Edozie, Otuokere Ifeanyi; Kamalesu, S.; Subramanian, R.; Raja, K.; Rameshkumar, S. (Applied organometallic chemistry, 2025)
In this study, a zinc-cytosine complex was synthesized by reacting zinc bromide with cytosine in a 1:2 molar ratio using propanol as the solvent. The crystalline complex dibromo-bis(cytosine)zinc(II) was structurally characterized using X-ray diffraction, confirming its molecular architecture. Molecular docking studies were conducted on three enzymes: Haemophilus influenzae (1GQY), Yersinia pestis RNA methyltransferase (3N4K), and Mycobacterium tuberculosis synthase (2O0D). The results revealed strong inhibitory potential against M. tuberculosis synthase, with hydrogen bonds formed with residues GLY 339 and significant steric interactions involving SER167 and PRO 125 hydrophobic interactions are observed with PRO 128 and ALA 166. Binding energies ranged from −6.6 kcal/mol, demonstrating robust interactions through hydrogen bonding and steric effects. The carbonyl group forms a conventional hydrogen bonding interaction with SER167 with distances of 2.21 Å. The hydrogen bonding CH bond interaction with PRO 125 and GLY 339 with distances of 3.42 and 3.42 Å. Drug-likeness evaluations using Lipinski's Rule of Five and ADME profiling indicated favorable attributes, such as good bioavailability, water solubility, and non-inhibition of cytochrome P450 enzymes. Computational analyses, including HOMO-LUMO gap and molecular electrostatic potential mapping, highlighted high reactivity and polarizability, with an energy gap of 0.8853 eV. These findings suggest the zinc-cytosine complex as a promising candidate for further drug development research.